The Role of Higher Education in Institutionalising Climate Change in Bangladesh - Alam, Gazi Mahabubul; Al‐Amin, Abul Quasem (2014)
Since the inception of higher education (HE) over one hundred years ago, its purpose has been to cater for the religious and social leaders who will be competent enough to run the country. Paradigm shifting in HE has made society realise that every profession demands competent professionals to provide balanced development across all educational sectors in order to see national development progress. As a result, universities now provide a wide range of training and education in the arts, sciences, social sciences and commerce, which may have caused the recent IT and e-commerce revolution. However, the primary contribution of HE is still seen as supporting economic development because it contributes less than other developmental phenomena. In developing nations, the issue of climate change is yet to be perceived either as an economic or as a social developmental agenda item. Consequently, HE provides less attention to climate change. However, climate change has a serious impact not only on economic development but also on social development. Therefore, HE needs to discover a concrete and substantial way in which to handle climate change. This novel piece of research, which is the first of its kind in Bangladesh, used qualitative methods in order to outline the policy direction that HE may adopt to make its role more distinct in handling climate change.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:institutionalising climate change; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12615 Geoengineering and Climate Ethics; openalex:import; openalex:yes

An Analysis of Animal Health and Veterinary Facilities in Coping the Climate Change in Bangladesh: What Education System can Offer for the Benefit - Al‐Amin, Abul Quasem; Alam, Gazi Mahbubul; Othman, Abdul Jalil Bin (Asian Journal of Animal and Veterinary Advances, 2011)
The current situation of climate change related to animal health impacts, overall awareness, mapping of livestock and national policy in these regards are needed an especial scholarly attention in Bangladesh. The national policy primarily fails to deal with the impacts of climate change on animal health and its danger sine it is virtually invisible tha the others harming events such as natural disasters. Therefore, this study addresses some issues generated through an analysis of animal health and veterinary facilities in coping with the climate change and also answer on how a sound effective policy can develop by overcoming the issue. This study focuses the lack of inter-linkage of national policy and planning including the shortcomings of current veterinary education system to bring together the climate change issue and impacts on animal health. The experiences of this study may utilize for climate change related to animal health impacts and a way forward for potential veterinary policy in Bangladesh.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:animal health; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12365 Effects of Heat Stress on Livestock Production; oa:topic:T12492 Emerging Zoonotic Diseases and One Health Approach; openalex:import; openalex:yes

An Analysis of Animal Health and Veterinary Facilities in Coping the Climate Change in Bangladesh: What Education System can Offer for the Benefit - Al‐Amin, Abul Quasem; Alam, Gazi Mahbubul; Othman, Abdul Jalil Bin (Asian Journal of Animal and Veterinary Advances, 2011)
The current situation of climate change related to animal health impacts, overall awareness, mapping of livestock and national policy in these regards are needed an especial scholarly attention in Bangladesh. The national policy primarily fails to deal with the impacts of climate change on animal health and its danger sine it is virtually invisible tha the others harming events such as natural disasters. Therefore, this study addresses some issues generated through an analysis of animal health and veterinary facilities in coping with the climate change and also answer on how a sound effective policy can develop by overcoming the issue. This study focuses the lack of inter-linkage of national policy and planning including the shortcomings of current veterinary education system to bring together the climate change issue and impacts on animal health. The experiences of this study may utilize for climate change related to animal health impacts and a way forward for potential veterinary policy in Bangladesh.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:animal health; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12365 Effects of Heat Stress on Livestock Production; oa:topic:T12492 Emerging Zoonotic Diseases and One Health Approach; openalex:import; openalex:yes

The Role and Responsibility of Education System in Ensuring Pharmacological and Medical Services for Animals and Livestock in Bangladesh: A Further Essence for Environment and Climate Change - Al‐Amin, Abul Quasem; Alam, Gazi Mahabubul; Hassan, Che Hashim; Othman, Abdul Jalil Bin (Journal of Animal and Veterinary Advances, 2012)
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10091 Malaria; oa:topic:T10211 Computational Methods in Drug Discovery; oa:topic:T14463 Impact of COVID-19 Pandemic on Health and Society; openalex:import; openalex:yes